Longitudinal changes in infants' rhythmic arm movements during rattle-shaking play with mothers - Laudanska, Zuzanna; López Pérez, David; Kozioł, Agata; Radkowska, Alicja; Babis, Karolina; Malinowska-Korczak, Anna; Tomalski, Przemysław (Frontiers in Psychology, 2022)
From early on, infants produce a variety of rhythmic behaviours - an ability that likely supports later social communication. However, it is unclear, how this rhythmic motor production changes with age. Here we investigated the coupling between infants’ arm movements across the first year of life in a social context of a rattle-shaking play with mothers. Through longitudinal measurements at 4, 6, 9 and 12 months of age using wearable motion trackers placed on infants' arms, we show that infants (N = 40) are similarly motivated to attempt rattle-shaking across the first year of life. However, with age, they make more rattling movements with an increased frequency. Their left and right arm movements become more coupled during rattle-shaking, as shown by an increase in wavelet coherence. Infants produced more rattling movements when they were rattling alone than when their mothers were rattling or singing simultaneously. There were no differences between infants’ individual and social rattling in between-arms coherence. Our results may help to understand rhythmic arm movements as precursors of motor social coordination.